Experiencing misinformation: The effect of pre-exposure warnings and debunking on psychic beliefs. Issue 6 (June 2023) - Kuhn, Gustav; Ortega, Jeniffer; Simmons, Keir; Thomas, Cyril; Mohr, Christine
Misinformation can have a detrimental impact on our beliefs, and it is therefore necessary to understand the cognitive mechanism by which false information is integrated or can be changed. In two experiments, we worked with fake psychic demonstrations, because observers easily adopt the experience as reflecting a "true" psychic event. We manipulated the availability of alternative explanations by providing a general warning that the performer is a magician with no psychic abilities (Experiment 1) or disclosing afterwards how the fake demonstration had been staged (Experiment 2). In Experiment 1, witnessing the psychic demonstration significantly increased participants' psychic beliefs, even though they had been warned. However, providing the alternative explanation about the deceptive method mitigated this effect. In Experiment 2, the realisation of deception significantly reduced participants' psychic beliefs directly after the performance and remained reduced 1 week later.